2011
DOI: 10.1188/11.onf.e409-e417
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnic Differences in Colorectal Cancer Screening Embarrassment and Physician Gender Preferences

Abstract: Discussing embarrassment and its causes, as well as providing an opportunity to choose a same-gender physician, may be promising strategies to reduce or manage embarrassment and increase CRC screening attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Embarrassment during the examination was the major reason for same-gender preference. This finding is also supported by other studies among male and female patients that found embarrassment as one of the major reason for same-gender preference [3, 4]. …”
Section: Discussionsupporting
confidence: 87%
“…Embarrassment during the examination was the major reason for same-gender preference. This finding is also supported by other studies among male and female patients that found embarrassment as one of the major reason for same-gender preference [3, 4]. …”
Section: Discussionsupporting
confidence: 87%
“…This finding is supported by other studies among male and female patients who identified embarrassment as one of the major reason for same-gender preference (Consedine et al, 2011;Shah et al, 2011;Varia et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In addition to CRC screening research testing the DPM which integrates cognitive and affective factors (Manne et al, 2003), research has examined the role of affect toward cancer, CRC, and screening (e.g., embarrassment, worry, fear, anticipated regret) in CRC screening decisions (Consedine, Magai, Krivoshekova, Ryzewicz, & Neugut, 2004; Consedine, Reddig, Ladwig, & Broadbent, 2011; Power et al, 2008; Rawl et al, 2000). Definitions of constructs from relevant health behavior theories included in the proposed framework are listed in Table 1.…”
Section: Colorectal Cancer Screeningmentioning
confidence: 99%
“…Negative affect associated with cancer and CRC screening has been suggested as a barrier to screening in both qualitative and quantitative research (Consedine et al, 2004; Consedine et al, 2011; Rawl et al, 2000). It is important to note that the relationship between affect and health behaviors is complex.…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 99%